2023
DOI: 10.1515/almed-2022-0098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on HbA1c management and results in pediatric and adult outpatients with diabetes

Abstract: Objectives Diabetes mellitus intensify the risks and complications related to COVID-19 infection. A major effect of the pandemic has been a drastic reduction of in-person visits. The aim of this study was to evaluate the impact of the COVID-19 pandemic on HbA1c management and results among pediatric and adult outpatients with diabetes, considering the laboratory and point-of-care testing (POCT) HbA1c measurements. Methods Obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 33 , 34 Remarkably, a study conducted in Spain in 2021 instead reported improved glycaemic control during the pandemic, and this was supported by two systematic reviews and meta-analyses performed in the United Kingdom and Germany in 2021. 35 , 36 , 37 In contrast to the findings of these studies, we found a significant increase in the average HbA1c result during the pandemic of 2.2 mmol/mol (0.2%) overall and in nine of the districts, indicating poorer glycaemic control during the pandemic where decreased numbers of HbA1c tests were being conducted. Notably, the Harry Gwala district, which had an increase of 31.8% in HbA1c tests performed during the pandemic, also demonstrated a significantly improved pandemic average HbA1c result.…”
Section: Discussioncontrasting
confidence: 99%
“… 33 , 34 Remarkably, a study conducted in Spain in 2021 instead reported improved glycaemic control during the pandemic, and this was supported by two systematic reviews and meta-analyses performed in the United Kingdom and Germany in 2021. 35 , 36 , 37 In contrast to the findings of these studies, we found a significant increase in the average HbA1c result during the pandemic of 2.2 mmol/mol (0.2%) overall and in nine of the districts, indicating poorer glycaemic control during the pandemic where decreased numbers of HbA1c tests were being conducted. Notably, the Harry Gwala district, which had an increase of 31.8% in HbA1c tests performed during the pandemic, also demonstrated a significantly improved pandemic average HbA1c result.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies found a decline in glycaemic control where up to 48.88% had poorly controlled diabetes (Biamonte et al., 2021; Robinson et al., 2020; Varma et al., 2021). However, not all studies have shown a worsening of glycaemic control in relation to the COVID‐19 lockdown; for example, studies carried out in Spain (Enguix et al., 2022; Oliver et al., 2023; Palanca et al., 2022) and other different European countries did not find a significant impairment (Bonora et al., 2020; Carr et al., 2021; Kofoed & Timm, 2022; Kowall et al., 2021; Ludwig et al., 2021). This fact could be explained by the increase in insulin prescription rates (Carr et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the effect of the pandemic on the control of patients with diabetes mellitus, finding inconsistent results (Abed Alah et al., 2021; Carr et al., 2022; Kaddar et al., 2022; Kofoed & Timm, 2022; O'Mahoney et al., 2022). In Spain, some studies carried out only in diabetic patients found no significant changes during the lockdown and post‐lockdown (Oliver et al., 2023; Palanca et al., 2022). However, to date, there are few studies that have evaluated the follow‐up over time of clinical parameters in chronic patients (Dehghani Tafti et al., 2023; Fikree et al., 2023), and none have jointly analysed the most common chronic diseases as well as the short‐ and medium‐term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lower acute physical activity adversely affected glycaemic control through a reduction in insulin sensitivity and lipid pro les, increased in ammation, and reduced muscle protein synthesis (Martinez-Ferran et al, 2020; Oliver et al, 2023) (13,14) COVID-19 alters the lipid pro le with lower TC, TG, LDL and HDL-C, which eventually regulates the cytokine and immune response. These lower pro les are associated with the severity and mortality of the cases (Chidambaram et al, 2022) ((15).…”
Section: Introductionmentioning
confidence: 99%